Drug use, public debate and increasing pressures for a drug policy reform in Finland - Hakkarainen, Pekka (Retreat or entrenchment?, 2021)
The situation in Finland is marked by a redistribution of labour between social and health care and criminal control policy. Attitudes are changing especially among the young, authorities are speaking out against the zero-tolerance policy, but there is also resistance to change. The situation is open.